A study of library consultancy in the Philippines - Mondonedo, Linda L. (1990)
This is a study of the activities of some fifty initially identified practicing library consultants. Thru a questionnaire survey, thirty-four answered the questionnaires, while the rest, were either not practicing or did not consider themselves as consultants. The questionnaires were followed up by personal interviews before the data were analyzed.